Biliary Microbial Structure of Gallstone Patients With a History of Endoscopic Sphincterotomy Surgery - Shen, Hongzhang; Zhu, Juanjuan; Ye, Fuqiang; Xu, Dongchao; Fang, Liangliang; Yang, Jianfeng; Lv, Huijie; Lou, Qifeng; Jin, Hangbin; Ni, Ming; Zhang, Xiaofeng (Frontiers in Cellular and Infection Microbiology, 2021)
The biliary microbiota is related to the pathogenesis of human bile duct stones. However, the extent to which a history of invasive endoscopic sphincterotomy (EST) affects the biliary bacterial community remains largely unknown. We collected bile samples from the common bile duct of 100 choledocholithiasis patients. We performed 16S rRNA sequencing to investigate and compare the biliary microbial community. The patients without antibiotic treatment (AT) were grouped into three clusters based on their biliary microbial compositions. The patients with a history of EST were significantly enriched in one cluster mainly consisting of gastrointestinal bacteria compared with the other two clusters consisting of oral and environmental bacteria. The β-diversities of patients with and without EST were also significantly different, whereas the α-diversities were comparable. The only significantly enriched bacterial genus associated with a history of EST was Pyramidobacter, while eight other genera were significantly decreased. For patients with AT, seven of these genera maintained their association with EST, including Pyramidobacter. However, after AT, the difference in β-diversities was diminished. EST induced a marked shift in the biliary microbial composition. A cluster of biliary bacteria was associated with a history of EST, and Pyramidobacter was specific to EST.